Computed Tomographic Morphometry of Lumbar Spine in Indian Population - Singh, Vivek; Prasad, Surya Nandan; Neyaz, Zafar; Bhargava, Nishant; Yadav, Uttam; Srivastav, Arun Kumar; Mishra, Prabhakar; Phadke, Rajendra Vishnu (Indian Journal of Neurotrauma, 2021)
Purpose Several studies have been conducted to determine morphometry of lumbar vertebrae, mostly in western population and data on other populations is relatively sparse. Most of these studies have been carried out using fresh cadavers or osteological collections and several of them having limitations such as a small sample size and lack of demographic information. We conducted morphometric analysis of the lumbar vertebrae in a relatively large number of Indian patients using computed tomography scan. Vertebral body and pedicle dimensions of lumbar spinal elements were documented in Indian population and compared with other studies from the subcontinent as well as from other parts of the world. The morphometric data thus compiled may help in the development of new spinal implants for transpedicular screw fixations.Methods An observational study was conducted and a total of 302 patients were evaluated. Thin section computed tomographic images of the 12th thoracic vertebra (D12) to 1st sacral vertebra (S1) were acquired and various dimensions of vertebral body and pedicle were recorded and analyzed.Results Generally, the lumbar vertebral and pedicle dimensions were found to be greater in male patients. Comparison of dimensions in different populations revealed statistically significant differences in pedicle dimensions between Indian population and others.Conclusion Morphometric analysis of lumbar vertebrae using computed tomography scan provides measurements of different vertebral dimensions. This will help in development of spinal implants in future to meet the specific needs of the studied population.
Keywords: CT morphometry; lumbar spine; pedicle width; vertebral height; interpedicular distance